Strike-slip shear zones of the Iberian Massif: Are they coeval? - Diez Fernandez, Ruben (2018)
Strike-slip shear zones of the Variscan orogen are used to derive the evolution of paleostrain and discuss the kinematics of the waning stages of the Gondwana-Laurussia collision during the amalgamation of Pangea. In the Iberian Massif, the recognition of three late Carboniferous deformation events related to strike-slip tectonics (D3, D4, D5) in the Trancoso-Pinhel region (Portugal) reveals that late orogenic transcurrent deformation was episodic and occurred in a short period of time (<15 m.y.). Early stages of strike-slip deformation included dextral and sinistral shear zones and orogen-parallel upright folds (D3; ca. 311 Ma). These structures followed the development of extensional shear zones (D2) during the tectonothermal reequilibration of the orogen. D3 structures were deflected and folded by the sinistral D4 Juzbado-Penalva do Castelo shear zone, dated as ca. 309–305 Ma by SHRIMP (sensitive high-resolution ion microprobe) U-Pb zircon dating of synkinematic granitoids. D3 and D4 structures were folded under east-west compression (D5) influenced by the strike-slip movement of the dextral Porto-Tomar shear zone. Variscan movement along the Porto-Tomar shear zone started ca. 304 Ma (onset of the Buçaco basin and syn-D5 granites), but ceased before ca. 295 Ma (age of the final closure of the Ibero-Armorican arc and crosscutting granites). The contrasting geometry, kinematics, and timing of these strike-slip shear zones are explained by deformation partitioning upon a rheologically inhomogeneous crust with structural and tectonothermal anisotropies generated during previous deformation. The convergence vector between Gondwana and Laurussia during D3–D5 remained the same, and was equivalent to the vector that explains the previous tectonic record (D2) in central and northwestern Iberia.